Etude épidémiologique et descriptive sur l’insuffisance rénale au niveau du CHU de Mostaganem et de l’EPH d’Oued Rhiou - Ghomari, Chahrazed Kheira; Sekmache, Hadjira (My University, 2022)
Chronic kidney disease (CKD) remains a silent disease that can occur without apparent symptoms for a long time and symptoms only appear at the terminal stage when dialysis or kidney transplantation must be used to stay alive. Our study aims to study the prevalence and severity of CKD according to age and sex and leads us to propose in perspective preventive measures to prevent subjects with CKD from reaching the terminal stage (hemodialysis treatment) .The biological analyses collected and analysed show anaemia (Hb=10.51 g/d1 and GR = 3.47 – 3.78 103/mm3) in men and women, respectively), hyperuremia (1.17 to 3.72 g/l) and hypercreatinemia (92.4 to 108.38 mg/l) in all patients; thus reflecting a fairly advanced impairment of kidney function. The hyperkalemia observed in elderly subjects suggests the adoption of a diet limited in potassium. Given the multiple underlying causes aggravating IRC, its management is therefore difficult especially at the last stage. The best way to prevent kidney disease before the terminal stage therefore remains the prospecting for markers.
Keywords: Kidney; chronic renal failure; Nephrons